Defects and grain boundary effects in MoS2: A molecular dynamics study. (January 2021) - Islam, Zahabul; Haque, Aman
Abstract: Mechanical properties of low-temperature large area chemical vapor deposited (CVD) transition metal dichalcogenides such as MoS2 are a function of crystallinity, which tends to deteriorate with the presence of grain boundaries (GBs) and defects. In this study, we report mechanical properties of polycrystalline as well as single crystal MoS2 containing defects and dopant atoms. To investigate mechanical properties we adopted computational approach using classical molecular dynamics (MD) simulation. Our calculated mechanical properties such as tensile strength, Young's modulus of single-crystal MoS2 are in good agreement with the existing literature and alter with the appearance of GBs and defects. Polycrystalline MoS2 samples exhibit GB strengthening i.e., Hall-Petch effects. A detailed investigation of a specific type of GB tilted sample also shows GBs insensitive fracture behavior. A small amount of sulfur vacancy and oxygen doping (<2%) exhibit ductility in the sample at the expense of failure strength. We also notice local plastic deformation which yields ductility in the sample. Our present study shows the detailed mechanism behind the plastic deformation behavior of single as well as polycrystalline sample. Graphical abstract: Image 1 Highlights: Mechanical properties of defective single crystal and polycrystalline monolayer MoS2 are investigated. Both vacancy defects and grain boundaries deteriorate mechanical properties of MoS2. Small amount of vacancy inclusion induce plasticity in the sample at the expense of tensile strength. Grain-boundary strengthening is observed in polycrystalline samples.